2008
DOI: 10.1001/jama.2008.824
|View full text |Cite
|
Sign up to set email alerts
|

Long-term All-Cause Mortality in Cancer Patients With Preexisting Diabetes Mellitus

Abstract: Context Diabetes mellitus appears to be a risk factor for some cancers, but the effect of preexisting diabetes on all-cause mortality in newly diagnosed cancer patients is less clear. Objective To perform a systematic review and meta-analysis comparing overall survival in cancer patients with and without preexisting diabetes. Data Sources We searched MEDLINE and EMBASE through May 15, 2008, including references of qualifying articles. Study Selection English-language, original investigations in humans wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
608
1
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 776 publications
(665 citation statements)
references
References 84 publications
(95 reference statements)
26
608
1
10
Order By: Relevance
“…Another study showed that individuals with diabetes and recent HbA 1c values >9.0% (75 mmol/mol; OR 1.5; 95% CI 1.3, 1.7) had higher mortality than those with recent 'normal' HbA 1c values between 6.5% (48 mmol/mol) and 9% (75 mmol/mol) [18]. Thus, the drop in MPR observed among patients with cancer in our study might have negatively influenced survival via the aforementioned mechanisms and may (partly) explain the established association between diabetes, cancer and survival [1][2][3].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Another study showed that individuals with diabetes and recent HbA 1c values >9.0% (75 mmol/mol; OR 1.5; 95% CI 1.3, 1.7) had higher mortality than those with recent 'normal' HbA 1c values between 6.5% (48 mmol/mol) and 9% (75 mmol/mol) [18]. Thus, the drop in MPR observed among patients with cancer in our study might have negatively influenced survival via the aforementioned mechanisms and may (partly) explain the established association between diabetes, cancer and survival [1][2][3].…”
Section: Discussionmentioning
confidence: 54%
“…Cancer patients with diabetes have a significantly higher overall mortality risk than those without diabetes [1][2][3]. To understand the association between diabetes and cancer, the American Diabetes Association and American Cancer Society reviewed the state of science regarding this in 2010 [4].…”
Section: Introductionmentioning
confidence: 99%
“…One point has become abundantly clear, and this is that cancer must now be numbered among the complications of diabetes. Furthermore, and as with ischaemic heart disease, cancer is associated with a higher mortality in those with diabetes than in those without [53]. Cancer risk and prevention may become increasingly important considerations in diabetes therapy, and the implications of the studies reported here are likely to be very far-reaching.…”
Section: Discussionmentioning
confidence: 84%
“…Increasing evidence also relates diabetes to a higher risk of cancer, including cancers of the pancreas, endometrium, liver, colorectum, and breast, possibly by mechanisms related to hyperinsulinema, hyperglycemia, and chronic inflammation 46. Furthermore, some studies found that diabetes may increase mortality in patients with cancer 47. Patients with cancer and pre-existing diabetes had a higher mortality than their non-diabetic counterparts, even after adjustment for BMI 48…”
Section: Discussionmentioning
confidence: 99%